Prevalence and correlates of pain and associated depression among community‐dwelling older adults: Cross‐sectional findings from LASI, 2017–2018. Issue 2 (30th December 2021) - Muhammad, Thalil; Rashid, Muhammed
Abstract: Background: Health practitioners often meet older persons suffering both from pain and depression. The study aimed to examine the factors associated with pain among older individuals and its association with major depression. In addition, the interaction between self‐rated health (SRH), wealth status, and pain that is associated with depression are explored. Methods: We used data from the Longitudinal Aging Study in India (LASI). Participants included 15, 098 male and 16, 366 female adults aged 60 years or older. Univariate and bivariate analyses along with χ 2 tests were conducted in the initial stage. Binary logistic regression analyses were performed to fulfill the objectives. Major depression was calculated using Short Form Composite International Diagnostic Interview. Results: A proportion of 39.6% older individuals ( n  = 12, 686) reported pain and 8.7% older adults ( n  = 2657) suffered from depression. Older adults who suffered from pain frequently were more likely to be depressed than those who never suffered from pain (adjusted odds ratio [AOR]: 1.70; confidence interval [CI]: 1.38–2.09). The interaction of pain, SRH, and household wealth status on depression found that older adults with pain who reported poor SRH (AOR: 4.18; CI: 3.50–5.00) or belonged to rich households (AOR: 2.27; CI: 1.84–2.80) had higher odds of suffering from depression, compared to older adults with no pain and good SRH or no pain and belonged to poor households. Conclusion: It is highlighted that pain is quite common in older people, and is linked to depression especially among older people with poor SRH. Thus, routine evaluation of pain and associated symptoms of mental illnesses should be performed for ensuring healthy aging.